2016
DOI: 10.1002/jmri.25224
|View full text |Cite
|
Sign up to set email alerts
|

Breathing maneuvers as a coronary vasodilator for myocardial perfusion imaging

Abstract: In conclusion, a voluntary long breathhold after hyperventilation leads to an increase of the myocardial perfusion reserve index. This may impact findings from current practice of first-pass perfusion imaging. The clinical utility of breathing maneuvers as a vasodilatory stimulus for first-pass perfusion imaging may warrant further research. J. MAGN. RESON. IMAGING 2016;44:947-955.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The primary aim of this retrospective pooled analysis was to investigate differences in the heart rate responses to a short period of hyperventilation between controls and patients with cardiovascular disease. Data was collected from studies that were conducted between 2010 and 2018 at the Bern University Hospital in Switzerland, the Stephenson Cardiac Imaging Centre, the Montreal Heart Institute, and the McGill University Health Centre in Canada 1921,4547 (NCT03050346, NCT02233634 of original studies). Hemodynamic responses to HR was not the defined end-point in any of the original studies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary aim of this retrospective pooled analysis was to investigate differences in the heart rate responses to a short period of hyperventilation between controls and patients with cardiovascular disease. Data was collected from studies that were conducted between 2010 and 2018 at the Bern University Hospital in Switzerland, the Stephenson Cardiac Imaging Centre, the Montreal Heart Institute, and the McGill University Health Centre in Canada 1921,4547 (NCT03050346, NCT02233634 of original studies). Hemodynamic responses to HR was not the defined end-point in any of the original studies.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, cardiovascular magnetic resonance (CMR) studies by our groups and collaborators have used hyperventilation as a tool to investigate myocardial oxygenation and heart disease 1921 . CMR, while considered the gold standard modality for many cardiac function and tissue parameters, is not suitable as an initial diagnostic or screening test because of the associated cost.…”
Section: Introductionmentioning
confidence: 99%
“…This was paralleled by marked regional differences of myocardial oxygenation during the HVBH maneuver between hypoperfused and remote myocardium. Furthermore, this was matched by a healthy volunteer study which showed the same breathing maneuver could induce a change in myocardial blood flow, as assessed by first pass perfusion CMR[ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a potential disadvantage, changes of the saturation of incoming blood and of the cardiac workload during the maneuvers could be confounders. Of note, breathing patterns may also affect other current myocardial perfusion techniques[ 13 ], for example with varying durations of breath-holds during CMR or CT scans or hyperventilation in anxious patients during cardiology tests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation